Precocious puberty in Turner Syndrome: report of a case and review of the literature - Improda, Nicola (BioMed Central, 2012)
INTRODUCTION: Turner Syndrome (TS) is caused by monosomy or structural abnormalities of the X chromosome, with a prevalence of about 1/2000 females live birth. Most important clinical features of TS are short stature and gonadal failure. Approximately one third of girls with TS may undergo spontaneous puberty. Here we report on the case of a girl with a rare 45X0/47XXX mosaic TS exhibiting a precocious puberty. CASE REPORT: The patient was diagnosed with TS at the age of 4 years, upon a diagnostic work-up for dysmorphic features. Chromosome analysis revealed a mosaic karyotype (45X0/47XXX). She presented with normal height and normal growth velocity so that Growth Hormone (GH) therapy was not started. She was referred to our Department at the age of 7 years and 10 months, because of vaginal bleeding. A physical examination revealed a Tanner stage III for breast and Tanner stage III for pubic hair development. Height and weight were within the normal range for age. Psychological evaluation showed moderate global developmental delay, together with emotional and social immaturity and reading difficulties. The growth rate was accelerated. Her bone age was 10 years. Pelvic ultrasound demonstrated increased size for age of both the uterus and the ovaries, with bilateral ovarian follicles. GnRH stimulation test revealed pubertal response of gonadotropins (peak LH 22.5 mIU/ml). MRI of the brain was normal. These clinical, radiologic and laboratory findings were consistent with a diagnosis of idiopathic central precocious puberty; therefore, GnRH analog therapy was started, in order to slow pubertal progression and to preserve adult stature. Furthermore, GH treatment was added to further improve adult height. CONCLUSION: Our case highlights the possibility of precocious puberty as an atypical clinical feature of TS. Thus, precocious puberty may occur in TS girls when a dosage compensation by the cell line with more than two X chromosomes allows normal ovarian function. GnRH analog therapy in addition to GH treatment should be recommended in TS girls with precocious puberty in order to slow pubertal progression and to preserve adult stature.